Effutu Asafo: Its organization and music - Turkson, A. A. (International Library of African Music, 1982)
Asafo is an ancient warrior organization that exists in all Akan societies of Ghana. When asafo came into existence can only be speculated on since there are no records to consult. One thing that is certain about it is the reason for its existence: it started as a force to initiate or combat aggression in time of war. The musical study of a people ought to be accompanied by a study of the culture of that people, for music involves culture and may be said to be culture bound. Such a study will provide an in depth understanding of the behaviour patterns of the people in music. The function of music in a society is a most fascinating subject and deserves thorough research. Effutu asafo certainly has a significant function in the society. The role of their music is many fold. The song texts and drum texts serve as a source of inspiration to the society and may also refer to historical facts about the society. The value of asafo song text as an indicator of historical events cannot be disputed;but its value depends on the reliability of oral tradition.
Keywords: African Music